2022
DOI: 10.3390/pharmaceutics14030532
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A2 mRNA Expression Rather than Genetic Variants Indicate Hepatic CYP1A2 Activity

Abstract: CYP1A2, one of the most abundant hepatic cytochrome P450 enzymes, is involved in metabolism of several drugs and carcinogenic compounds. Data on the significance of CYP1A2 genetic polymorphisms in enzyme activity are highly inconsistent; therefore, the impact of CYP1A2 genetic variants (−3860G>A, −2467delT, −739T>G, −163C>A, 2159G>A) on mRNA expression and phenacetin O-dealkylation selective for CYP1A2 was investigated in human liver tissues and in psychiatric patients belonging to Caucasian popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 72 publications
1
10
0
1
Order By: Relevance
“…2 A). We have previously demonstrated that CYP1A2 expression rather than CYP1A2 genotype indicated hepatic CYP1A2 activity 35 ; therefore, the association between CYP1A2 mRNA levels in the patients’ leukocytes and olanzapine concentration was also established. Due to the low number of high CYP1A2 expressers, in statistical analysis, high and normal expressers were combined.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2 A). We have previously demonstrated that CYP1A2 expression rather than CYP1A2 genotype indicated hepatic CYP1A2 activity 35 ; therefore, the association between CYP1A2 mRNA levels in the patients’ leukocytes and olanzapine concentration was also established. Due to the low number of high CYP1A2 expressers, in statistical analysis, high and normal expressers were combined.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic DNA was isolated from peripheral blood samples by Quick-DNA™ Universal Kit (Zymo Research, Irvine, CA). Hydrolysis SNP analyses were performed by TaqMan assays for CYP1A2 SNPs [− 3860G > A (rs2069514), − 2467delT (rs35694136), − 739T > G (rs2069526), − 163C > A (rs762551) and 2159G > A (rs2472304)] and for CYP2D6 SNPs [2549delA (rs35742686), 1846G > A (rs3892097), 1707delT (rs5030655), 2615-2617delAAG (rs5030656), 100C > T (rs1065852) and 2988G > A (rs28371725)] 34 , 35 . CYP2D6 gene deletion and CYP2D6 allele specific duplication/multiplication were determined as previously described 34 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations